2006
DOI: 10.1016/j.acn.2006.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Improving the clinical utility of the SIRS cognitive items: Preliminary reliability, validity, and normative data in pretrial and clinical samples

Abstract: The utility of the Structured Interview of Reported Symptoms [SIRS; Rogers, R., Bagby, R. M., & Dickens, S. E. (1992). Structured Interview of Reported Symptoms professional manual. Odessa, FL: Psychological Assessment Resources], Improbable Failure Rate (IF) scale in pretrial (N=64) and clinical (N=153) samples was explored. Internal consistencies of the IF items were alpha=.81 and alpha=.92, respectively, with split-half reliabilities of .89 and .84, respectively. The IF scale loaded distinctly from the SIRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Based on the floor-effect detection strategy, IF consists of 20 items requiring provision of antonyms (10) or rhymes to very simple words (10). Despite the organization into antonyms and rhymes, initial data suggest that these items may form a single dimension (Rogers, Jackson, Sewell, & Salekin, 2005;Wynkoop, Frederick, & Hoy, 2006) and be potentially effective for detecting cognitive feigning (Wynkoop et al, 2006). However, relatively little research has evaluated the effectiveness of the IF scale against established measures of FCI.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the floor-effect detection strategy, IF consists of 20 items requiring provision of antonyms (10) or rhymes to very simple words (10). Despite the organization into antonyms and rhymes, initial data suggest that these items may form a single dimension (Rogers, Jackson, Sewell, & Salekin, 2005;Wynkoop, Frederick, & Hoy, 2006) and be potentially effective for detecting cognitive feigning (Wynkoop et al, 2006). However, relatively little research has evaluated the effectiveness of the IF scale against established measures of FCI.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, nonintellectually impaired individuals feigning deficits, and intellectually impaired individuals, performed similarly. For these reasons, in contrast to Wynkoop and colleagues’ (2006) recommendation, the researchers concluded that the IF scale should not be used as a screening measure of FCI. Rogers and colleagues (2009) advocated for the use of a revised version of the IF scale (i.e., IF-revised), that included only items with specificities over 90%, and used a cutoff score of zero to identify genuine participants.…”
Section: The If Scalementioning
confidence: 86%
“…These results cannot be conclusively interpreted as evidence of feigning but suggest patients classified as probable feigning on the SIRS are more likely to also feign cognitive impairment. To provide an additional test for this hypothesis, we evaluated the Improbable Failure (IF) rate scale (Rogers et al, 1992;Wynkoop, Frederick, & Hou, 2006), which consists of four groups of five items measuring an individual's ability to complete simple cognitive tasks. As noted by Wynkoop et al (2006), the IF scale relies on the floor effect detection strategy, with errors indicative of feigned cognitive impairment.…”
Section: Feigned Cognitive Impairmentmentioning
confidence: 99%
“…To provide an additional test for this hypothesis, we evaluated the Improbable Failure (IF) rate scale (Rogers et al, 1992;Wynkoop, Frederick, & Hou, 2006), which consists of four groups of five items measuring an individual's ability to complete simple cognitive tasks. As noted by Wynkoop et al (2006), the IF scale relies on the floor effect detection strategy, with errors indicative of feigned cognitive impairment. Notably, the items on the IF scale are not used to classify patients as honest responders or probable malingerers.…”
Section: Feigned Cognitive Impairmentmentioning
confidence: 99%